GAMBARAN FUNGSI KOGNITIF PADA LANSIA YANG MELAKUKAN SENAM - Siagian, Lina Maria; Arneliwati, Arneliwati; Hairani Damanik, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The elderly refers to ages nearing or surpassing the life expectancy of human being, categorized as above 60 years. The elderly experience the aging process resulting in decreased function of the body such as cognitive function. Age-related change in cognitive function are attention, working memory, long-term memory, perception, etc. This research aimed to portray how gymnastic practice affects cognitive function in elderly at Harapan Raya Health Centre. The design of research was descriptive that explain about characteristics respondent, training program, and cognitive function in elderly. The sample of this research was 40 respondents taken based on inclusion criteria using total sampling technique. Montreal Cognitive Assessment sheet (MoCa-Ina) applied to measure cognitive performance and a questionnaire for their exercise program. The results showed there were 21 respondents (52.5%) did gymnastics 3 times a week, 34 respondents (85%) did gymnastics 20-60 minutes per session, 19 respondents (47.5%) did fitness for elderly, and as much as 28 respondents (70%) had cognitive impairment. Most of them had experienced cognitive impairment. Based upon this studies, the researcher suggest to increasing physical activity with promoting memory exercises for elderly in order to reduce risk of poor cognition.Keywords: Cognitive function, Elderly, Gymnastics